The Tuning of a CFD Model for External Ballistics, Followed by Analyses of the Principal Influences on the Drag Coefficient of the .223 Rem Caliber - Jiří Maxa; Pavla Šabacká; Robert Bayer; Tomáš Binar; Petr Bača; Jana Švecová; Jaroslav Talár; Martin Vlkovský; Lenka Dobšáková (Technologies)
This paper presents the subject of external ballistics. The presented research employs a contemporary methodological approach, integrating theoretical analysis, CFD simulations, and experimental measurements. External ballistics is characterized by a wide spectrum of physical phenomena that influence projectile trajectory. This contribution focuses on the analysis of drag force acting on a .223 rem caliber projectile in both subsonic and supersonic regimes. Based on experimental findings, a CFD model was refined and subsequently used to evaluate the drag force and drag coefficient, with a comparative analysis performed against G1 and G7 ballistic coefficient functions. Furthermore, the effect of the barrel length on the resultant outcome was assessed. The validated CFD model was employed to analyze the characteristics of shock waves generated at the projectile’s nose and their impact on the drag force, along with the influence of ambient temperature, particularly within the supersonic domain.